The cost of providing consultative palliative care services in a tertiary hospital setting - Mbuthini, Linda (Department of Public Health and Family Medicine, 2021)
Background The Sub-Saharan African region has sparse palliative care established to cater for patients facing life limiting conditions. In South Africa, costing frameworks for palliative care interventions for the public sector do not exist and the cost of running a comprehensive palliative care programme remains unknown. There are few costing studies to inform costs of palliative care models which are necessary for decision makers to base their decisions on. The aim of this study was to determine the costs and cost drivers for hospital based consultative palliative care service (HBPCS) in South Africa adopting a providers' perspective. Methods In this empirical costing study, we developed and utilised a costing tool that employed a mixed bottom-up and top-down costing method to estimate the incremental cost of an existing hospital based consultative palliative care services (HBCPCS) in a tertiary hospital in Cape Town, South Africa, called Groote Schuur Hospital (GSH) adopting a public provider perspective. All inputs where valued using bottom-up, ingredients-based methods, except for direct staff where a top-down approach was utilised to allocate the staff's full salary to palliative care services. We collected costing data by conducting inventory audits, key informant interviews and observations. All inputs required in the production of the HBCPCS were checked against a costing framework for economic evaluations of palliative care interventions to ensure that the cost estimates were as inclusive as possible. All inputs with a lifespan of more than one year were annuitized using a 3% rate. Results The total annual cost for running the HBCPCS was R2 494 419 including both recurrent and capital costs. Recurrent items alone accounted for 96% (R2 392 407). While capital items accounted for 4% (R102 013) during the study period. The total cost per visit was R642 including the standard drug treatment package (R16). The major cost driver in the service was personnel accounting or 91% of the total annual cost. While a scenario analysis shows that when the size of the team size is doubled then the cost of direct personnel would increase to R4.4 million. Conclusion We have estimated the incremental unit cost of HBCPCS to be R642 per visit, the major cost driver being personnel. If funding allows, with an annual cost of R2.4 million these services can be provided in a public tertiary hospital as an adjunct to inpatient care for patients as a strategy for integrating palliative care to general health care services, as has been done at GSH. The HBCPCS was less costly when compared to hospital-based outreach palliative care programmes.